1983
DOI: 10.2307/3429511
|View full text |Cite
|
Sign up to set email alerts
|

Metallic Elements in Fossil Fuel Combustion Products: Amounts and Form of Emissions and Evaluation of Carcinogenicity and Mutagenicity

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. The National Institute of Environmental Health Sciences (NIEHS) andBrogan & Partners are collaborating with JSTOR to digitize, preserve and extend access to Environmental Heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 25 publications
(26 reference statements)
0
28
0
Order By: Relevance
“…(8) DEP consist of carbonaceous nuclei, a vast number of organic chemicals, (9) and metals. (10) We have also demonstrated that DEP components augment the asthma model in vivo. (11) In brief, pulmonary exposure to DEP components has aggravated antigen-related airway inflammation characterized by infiltration of eosinophils and lymphocytes around the airway and an increase in goblet cells in the bronchial epithelium and the adverse effects have been more prominent with organic chemical components of DEP (DEP-OC) than with residual carboneous ones (washed DEP) with overall trend.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…(8) DEP consist of carbonaceous nuclei, a vast number of organic chemicals, (9) and metals. (10) We have also demonstrated that DEP components augment the asthma model in vivo. (11) In brief, pulmonary exposure to DEP components has aggravated antigen-related airway inflammation characterized by infiltration of eosinophils and lymphocytes around the airway and an increase in goblet cells in the bronchial epithelium and the adverse effects have been more prominent with organic chemical components of DEP (DEP-OC) than with residual carboneous ones (washed DEP) with overall trend.…”
Section: Introductionmentioning
confidence: 95%
“…(1,2) The concentration of PM with a mass median aerodynamic diameter (a density-dependent unit of measure used to describe the diameter of the particle) ≤ 10μm (PM 10 ) is related to daily hospital admissions for several respiratory diseases. (3) Additionally, recent data have shown that PM with a mass median aerodynamic diameter ≤ 2.5μm (PM 2.5 ) are more closely associated with both acute and chronic respiratory effects and subsequent mortality than PM 10.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the cadmium that occurs in air is associated with particulate matter in the respirable range (0.1-1 m diameter), and its residence time is relatively short (days to weeks) but sufficient to allow long-range transport in the atmosphere [7]. Cadmium is recognized as a potential human carcinogen [8], and the State Environmental Protection Administration of China has set its emission standard from MSW incinerators at 0.1 mg/m 3 [9].…”
Section: Introductionmentioning
confidence: 99%
“…Tungsten concentrations in ambient air are generally less than 1 ng m −3 , but increase moderately in urban, mining/metal processing areas. Air sampling studies over six U.S. cities report atmospheric levels of tungsten in the range of 0.1-2.0 g m −3 [48], while other studies performed in urban areas of East Chicago, Indiana and Montreal, Que., Canada have reported values of 6.0 and 5.2 ng m −3 , respectively [49,50]. A more systematic study conducted in eight urban areas of Canada reported a mean W concentration of 0.0039 g m −3 in the particulate fraction (PM 2.5 ) of atmospheric samples [51].…”
Section: Atmospheric Systemsmentioning
confidence: 98%